Technology as an enabler of a new ecosystem responsive urbanism. ﻿Interview with Caro Ratti (CRA Studio) - Giorgia Tucci; Carlo Ratti Associati (Agathón)
In recent decades, the growing awareness of the exhaustibility of our planet’s resources has placed sustainability at the centre of current global policies that, to cope with the complex international situation, have set goals for sustainable development, promoting actions that provide ecological, digital and social innovation. The increasing contamination of digital technology in the urban context has led to reflections on urban reformulation processes and innovative actions promoting the global transition process. The new urban and territorial approach is moving towards a new paradigm of integration between artificial and natural, technology and sustainability, digital and ecology. Testimony to this transition is the transdisciplinary approach in the design and experimentation of the international practice of Carlo Ratti Associati (CRA).